STUDI KOMPARATIF PENILAIAN KINERJA KEUANGAN PEMERINTAH DAERAH PADA SAAT PANDEMI COVID-19 DAN SESUDAH PANDEMI COVID-19 - Yulianti, NA; Wicaksono, Dimas (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2024)
This research aims to determine the financial performance of local governments during the Covid-19 pandemic and after the Covid-19 pandemic. The samples used in this study were regencies/cities in West Java Province registered on the West Java PPID website and reported budget realization reports in 2020-2023 with 13 sample regencies/cities using the comparative method. The variables of this study are the financial performance of local governments as measured by the effectiveness ratio, efficiency ratio, harmony ratio, growth ratio, and independence ratio. The results show that the regional effectiveness ratio has a significant difference in regional financial performance during the Covid-19 pandemic and after the Covid-19 pandemic. Meanwhile, the efficiency ratio, harmony ratio, growth ratio, and regional independence ratio do not have any significant differences in regional financial performance during the Covid-19 pandemic and after the Covid-19 pandemic.